Impact of Etch Process on Hafnium Dioxide Based Nanoscale RRAM Devices. (25th August 2016) - Beckmann, Karsten; Holt, Josh; Olin-Ammentorp, Wilkie; Van Nostrand, Joseph; Cady, Nathaniel
Abstract : Resistive Random Access Memory (RRAM) is a novel form of non-volatile memory that is expected to play a major role in future computing and memory solutions. We have developed memristive RRAM devices and integrated logic devices on a 300mm wafer platform with the IBM 65nm 10LPe process technology. The RRAM device consists of an inert tungsten bottom electrode, HfO2 based active switching layer, a Ti oxygen exchange layer and a TiN top electrode. The TiN/Ti capping layers were etched with reactive ion etch (RIE), whereas two approaches were tested for the HfO2 removal: a wet etch with diluted hydrofluoric acid, and a BCl3 /O2 based RIE process. The impact on the RRAM devices for both etch processes was investigated with respect to the physical structure, the electrical characteristics, and yield. The electrical characteristics include simple I-V DC sweeps and pulse-based endurance measurements.